Are Employees Happier when Staying Connected with their Companies Outside Working Hours?. (August 2022) - Martin, Ludivine; Pénard, Thierry; Poussing, Nicolas
Information and communication technologies supported by mobile devices (laptops, smartphones, tablets) have enhanced the ability for employees to stay connected with their companies outside working hours. However, we have little understanding of the implications for employees' subjective well-being. This paper aims to analyze the impact of two forms of digital connection on subjective well-being: online communication through email and smartphone (communication technologies), and remote access to companies' networks, that is, files, management systems, and software (information technologies). In order to asses this, we use a large survey on the working conditions and work quality of 14, 685 employees in Luxembourg. Results show that being contacted regularly outside office hours has a negative impact on life satisfaction, whereas remote access to the companies' networks is positively related to life satisfaction and negatively related to job stress.